Concept mapping for learners of all ages - Nancy L. Gallenstein (Universidad de Granada, 2013)
Concept mapping is an inquiry technique that provides students at all ages with opportunities to demonstrate learning through performance. A concept map refers to a graphic/visual representation of concepts with linking connections that show various relationships between concepts (Novak & Gowin, 1984). Assessment is an ongoing process integrated with instruction across subject areas. The National Council of Teachers of Mathematics (NCTM) emphasizes that assessment should focus on both the enhancement of student learning as well as serve as a valuable tool for making instructional decisions (NCTM, 2000). Assessment activities can take on a variety of forms, one being performance tasks. In this manuscript, an explanation of concept mapping is provided for learners ages 3 - 12 along with several examples of concept maps for young learners, including examples from an assessment project in the subject area of mathematics. Also presented are the numerous benefits of the concept mapping technique for both students and teachers.